Treatment of chronic hepatitis B: options, monitoring, special cases and adverse effects - Mateusz Litwin Litwin; Agnieszka Mikosińska; Jakub Parys; Patrycja Kałuziak; Aleksandra Witek; Martyna Kaźmierczak; Stanisław Jesionek; Marta Jajczak; Maciej Mossakowski (Journal of Education, Health and Sport)
Introduction: